Lean Six Sigma effect on the Quality of the Products in Jordanian Food Companies: The Moderating Role of the Manufacturing Process - Majd Mohammad Omoush (International Review of Management and Marketing, 2020)
The purpose of this study is to determine the effect of lean six sigma and the quality of the product and manufacturing process. Further, its focus on understanding the impact on the defect, over production, Motion, Waiting time, through the role of Manufacturing Process on quality of products. The study applied the questionnaire, which was adapted from past literature. The questionnaire was distributed to a sample of 180 respondents, and the number of returned items was 142. The study applied a purposive sample that (employee) hold positions related to quality management, production, research and development (R&D) at Jordanian food industry. The data analysis was performed using Statistical procedures being used several methods were used, including the exploratory analysis, the global empirical analysis, the Cronbach alpha analysis, Impact coefficients (beta), and the arithmetic mean, standard deviation, multiple regression, to test moderating hypothesis the Process macro analyses. Accordingly, and based on a multiple regression analysis, the alternative hypothesis is adopted, concluding that the elements of lean six sigma influence the consistency of the goods excluding the variables of motion and waiting time from the respondent's point of view. As a consequence of the manufacturing process, the relationship between the lean six sigma variable and the quality of the product has a positive moderation effect.